The Relationship Between Actin Cytoskeleton and Membrane Transporters in Cisplatin Resistance of Cancer Cells - Shimizu, Takahiro; Fujii, Takuto; Sakai, Hideki (Frontiers in Cell and Developmental Biology, 2020)
Cisplatin [cis-diamminedichloroplatinum (II)] is a platinum-based anticancer drug widely used for the treatment of various cancers. It forms interstrand and intrastrand cross-linking with DNA and block DNA replication, resulting in apoptosis. On the other hand, intrinsic and acquired cisplatin resistance restricts its therapeutic effects. Although some studies suggest that dramatic epigenetic alternations are involved in the resistance triggered by cisplatin, the mechanism is complicated and remains poorly understood. Recent studies reported that cytoskeletal structures regulate cisplatin sensitivity and that activities of membrane transporters contribute to the development of resistance to cisplatin. Therefore, we focus on the roles of actin filaments and membrane transporters in cisplatin-induced apoptosis. In this review, we summarize the relationship between actin cytoskeleton and membrane transporters in the cisplatin resistance of cancer cells.